Strategi Fundraising “Program KOIN” BAZNAS dalam Masa Pandemi COVID-19 di Kabupaten Ngawi - Al Khudori, Mahfud; Humaidi, Muchtim (Institut Agama Islam Negeri Ponorogo, 2022)
The fundraising of “KOIN Program” of BAZNAS uses direct and indirect strategies to increase the generation this program, one of them is by rising awareness of government agencies and entrepreneurs. This study aims to determine the fundraising strategy also the supporting and the inhibiting factors of “KOIN Program” of BAZNAS in Ngawi Regency. This study uses descriptive qualitative method. Field research is the term for this type of research. Interviews, observations, and documentation were techniques used to obtain the data. The findings of this study were analyzed using a deductive approach, which begins with broad statements then leads to specific conclusions. The results of the study show that the fundraising strategies implemented by BAZNAS in Ngawi Regency during the COVID-19 pandemic are pick-up fundraising and fundraising at local government events. The inhibiting factors for the implementation of fundraising is the lack of public and official government officers’ awareness regarding BAZNAS’s “KOIN Program” and there is competition with other institutions. While the supporting factors of the program are BAZNAS received full support from government agencies and entrepreneurs in Ngawi Regency. Fundraising “Program KOIN” BAZNAS menggunakan strategi langsung dan tidak langsung untuk meningkatkan hasil fundraising program ini, salah satunya dengan menambahkan sosialisasi ke instansi pemerintah dan pengusaha. Penelitian ini bertujuan untuk mengetahui strategi fundraising dan faktor pendukung serta penghambat “Program KOIN” BAZNAS di Kabupaten Ngawi. Penelitian ini menggunakan metode deskriptif kualitatif. Penelitian lapangan adalah istilah untuk jenis penelitian ini. Teknik wawancara, observasi, dan dokumentasi digunakan untuk memperoleh data penelitian. Hasil penelitian ini dianalisis dengan menggunakan pendekatan deduktif yang dimulai dengan pernyataan yang luas, kemudian mengarah kepada kesimpulan yang spesifik. Hasil kajian penelitian menunjukkan bahwa strategi fundraising “Program KOIN” yang dilaksanakan BAZNAS Kabupaten Ngawi pada masa pandemi COVID-19 adalah: fundraising jemput bola dan fundraising di acara-acara pemerintah daerah. Faktor penghambat dari pelaksanaan fundraising adalah kesadaran masyarakat dan ASN mengenai “Program KOIN” BAZNAS yang masih kurang dan persaingan dengan lembaga lain. Sedangkan, faktor pendukung program adalah BAZNAS mendapat dukungan penuh dari instansi pemerintah dan pengusaha-pengusaha di Kabupaten Ngawi.